The Digipolitical and African Political Thought - Claudia Favarato (Weizenbaum Journal of the Digital Society, 2025)
Today, digitality is pervasive across all spheres of human social and political life. To inquire into digital-engendered ontologies, this paper presents a theoretical framework undergirding African political thought for the study of the political sphere in digitality, or the digipolitical. This neologism refers to the political as an ontological category redefined via its intersection with the digital. This understanding rests on three premises: the characteristics of the digital, a sui generis virtual reality; the algorithmic architecture of the cyber socio-political space; and the onto-relational nature of the political subjects, which entails the interplay of the analogue with digital-humans. Regarding more recent disciplines and theories, such as posthumanism, this paper brings to the fore insights offered by African political thought, which has long emphasized reading individuals, communities, and structures of power through the lens of the political centered on the concept of relationality. I defend the assertion that the relational approach inscribed in African political philosophies offers valuable insight into digital political onto-relationalities, as it discloses power from in-between spaces and details its dynamics.